Educação ambiental à distância nas redes e processos de formação, currículos e subjetivação - Porto, Atonildo Pereira (2013)
The survey "Environmental Education at a distance - in networks and processes of formation, curriculum and subjectivation" is movement in cartography of conversations and narratives in networks woven and in constitution in everyday learning environments. The major objective of the research is in thinking and problematize the continued training of educators in Environmental Education from the provision of first process trainer in Environmental Education at a distance - PFEA@D - offered in Brazil between the years 2009 and 2010. The production of data intake was found in the documents of the trainer process and its outcomes in school. In the different spaces-times, AVA and the school environment, the productions of sujeitosmosaicos moved thoughts and practices. In the dialogs with others, in the workshops, in the classroom and in conversations with sujeitosmosaicos we find clues and devices which potentiate the life, that make us think Environmental Education as processes, invention and truths in times crossed by technology, also as a possibility of a better world ahead the environmental crisis in times of transitional paradigm. The problematization are still flows in philosophy, in paradigms of complexity and chaos, in the ideas of many authors, in knowledge-doing networks and subjectivities of educators and students that emerge between the possible...real...current...virtual networks of environmental education. The experiences with the PFEA@D did emerge other curriculum, created possibilities, linesof escape. Processes of subjectivation produced relevant to understanding the formation of sujeitosmosaicos. Possibly educators and students were crossed for the affections and desires that touched, intervened in their relationships, knowledge and practices in environmental education and transformed their perceptions of/in the world.